r-neutrosophic subset of G-submodules - BINU R (Big Data and Computing Visions)
This article explains a particular category of neutrosophic subsets of G-submodules, specifically r-neutrosophic subsets, where r ∈ [0, 1]. The algebra of r-neutrosophic subsets of G-submodules is dis-cussed, along with some fundamental characteristics of their sum. Definitions and theorems related to this concept are provided to clarify the properties of an arbitrary non-empty family of r-neutrosophic subsets of G-submodules.